Enzymatic Hydrolysis of Egg White Protein Exerts a Hypotensive Effect in Spontaneously Hypertensive Rats - Lee, Da-Eon; Jung, Tae-Hwan; Jo, Yu-Na; Yun, Sung-Seob; Han, Kyoung-Sik (Food science of animal resources, 2019)
This study was conducted to investigate the hypotensive effect of egg white protein (EWP) hydrolysate (EWH) in spontaneously hypertensive rats (SHRs). The hydrolysis of EWP was effectively performed with a combination of 0.5% bromelain and 1% papain at 50°C for 60 min. The resulting hydrolysate did not elicit an allergic reaction as confirmed by human mast cell activation test. The systolic and diastolic blood pressures of the SHRs fed the EWH diet were observed to be significantly or numerically lower than those of the other groups during the experimental period of 28 d. EWH treatment significantly (p<0.05) upregulated the nitric oxide levels in hCMEC/D3 cells and the plasma of the SHRs compared to those in the control. Moreover, EWH ingestion significantly (p<0.01) reduced the plasma angiotensin II level of the SHRs compared with that in the control. In conclusion, beyond its basic nutritional value, EWH prevents and manages hypertension, and thus can be an invaluable resource for functional food development.